ClinClip: a Multimodal Language Pre-training model integrating EEG data for enhanced English medical listening assessment - Sun, Guangyu (Frontiers in Neuroscience, 2025)
IntroductionIn the field of medical listening assessments,accurate transcription and effective cognitive load management are critical for enhancing healthcare delivery. Traditional speech recognition systems, while successful in general applications often struggle in medical contexts where the cognitive state of the listener plays a significant role. These conventional methods typically rely on audio–only inputs and lack the ability to account for the listener's cognitive load, leading to reduced accuracy and effectiveness in complex medical environments.MethodsTo address these limitations, this study introduces ClinClip, a novel multimodal model that integrates EEG signals with audio data through a transformer-based architecture. ClinClip is designed to dynamically adjust to the cognitive state of the listener, thereby improving transcription accuracy and robustness in medical settings. The model leverages cognitive-enhanced strategies, including EEG-based modulation and hierarchical fusion of multimodal data, to overcome the challenges faced by traditional methods.Results and discussionExperiments conducted on four datasets–EEGEyeNet, DEAP, PhyAAt, and eSports Sensors–demonstrate that ClinClip significantly outperforms six state-of-the-art models in both Word Error Rate (WER) and Cognitive Modulation Efficiency (CME). These results underscore the model's effectiveness in handling complex medical audio scenarios and highlight its potential to improve the accuracy of medical listening assessments. By addressing the cognitive aspects of the listening process. ClinClip contributes to more reliable and effective healthcare delivery, offering a substantial advancement over traditional speech recognition approaches.